(untitled) (Research, Society and Development, 2020)
The obstacles faced in learning stereochemistry include difficulties related to visualization, problems in the acquisition and mastery of concepts that are prerequisites for understanding and differentiating stereoisomers. It is important to highlight that cognitive learning contributions consider that the student learns what is meaningful to him; for this reason, contextualization has a fundamental role in the conceptualization process. This work aims to present a systematic review of the literature on teaching of stereoisomerism seeking to identify strategies and themes used. The search method consisted of the selection of studies published in journals in the last 20 years, in Portuguese and Spanish, with Qualis A1 and A2 in the teaching area, in addition to the articles from Química Nova na Escola. Those that included stereoisomers in organic compounds were included as the central theme, presenting strategies or themes for their contextualization in teaching. Based on Content Analysis, the analytical process of the sixteen articles selected based on the criteria resulted in the creation of categories: scope of the article, teaching strategies, didactic resources for visualization and themes used. The results indicate the focus on the publication of teaching proposals, strategies for the development of visual skills using molecular kits and applications, and the drugs theme being the most used for contextualization. As a general synthesis, we found the use of resources for visual literacy, in addition to the contextualization that privileges a variety of situations in which the concept of stereoisomerism is applied, having the potential to make it meaningful for students.